Clinical evaluation of the Immulite® 1000 chemiluminescent immunoassay for measurement of equine serum insulin - Go, Yun Young; Hazard, Nicole W.; Balasuriya, Udeni B. R.; Chapman, Anna M.; Fitton, Nanette S.; Kenéz, Ákos; Andrews, Frank M. (Frontiers in Veterinary Science, 2023)
Accurate quantitative analysis of equine insulin in blood samples is critical for assessing hyperinsulinemia in horses. Although there are various laboratory methods for evaluating equine serum insulin, different immunoassays show significant discrepancies between the determined insulin concentrations and are often not comparable. The aim of this study was to evaluate the Immulite® 1000 chemiluminescent immunoassay (CLIA) to establish independent laboratory and assay-specific cutoff values to provide an accurate diagnosis of hyperinsulinemia in horses. Thus, the analytical and clinical performance of Immulite® 1000 CLIA in terms of precision (intra- and inter-assay coefficient of variance, CV) and recovery upon dilution were evaluated and compared with radioimmunoassay (RIA), which has been previously validated for use in horses. Archived serum samples (n= 106) from six Quarter horse mares enrolled in the glucose phase of a Frequently Sampled Insulin and Glucose Test (FSIGT) study were used to measure blood insulin. As results, the Immulite® 1000 CLIA had good precision with acceptable intra- and inter-assay CVs, adequate recovery on dilution, and a strong correlation with the RIA (r = 0.974, P < 0.0001), with fixed bias resulting in consistently lower values. On this basis, the Immulite® 1000 Insulin Assay is valid for measuring equine serum insulin for diagnostic and monitoring purposes when cutoff values are appropriately adjusted.